Split brake disc of wind power yaw brake and preparation method of split brake disc

By using aluminum alloy powder material and ceramic reinforced phase to make the wind power yaw brake split brake disc, the wear resistance and corrosion problems of ductile iron materials are solved, and higher salt spray corrosion resistance and lower maintenance costs are achieved. Extends service life and improves performance.

CN119289010APending Publication Date: 2025-01-10XEMC NEW ENERGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411409106.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The ductile iron materials in wind power yaw brakes have poor wear resistance, high maintenance costs, high material brittleness, and accelerate wear in offshore salt spray corrosion environments, resulting in a shortened service life of the brake disc and a decrease in braking performance.

Method used

The split brake disc is made of aluminum alloy powder material and ceramic reinforced phase material. Through the gradient design of the structural layer and friction layer, combined with pressurization and sintering treatment, a single-body brake with high salt spray corrosion resistance and high bonding strength is formed. and easy to discharge wear chips and oil stains through gap design.

Benefits of technology

It improves the salt spray corrosion resistance and wear resistance of the brake disc, extends the service life, reduces maintenance costs, and improves the stability and performance of the brake disc by enhancing the interface combination strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119289010A_ABST
    Figure CN119289010A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of brake discs, in particular to a split brake disc of a wind power yaw brake and a preparation method of the split brake disc. The split brake disc comprises a plurality of arc-shaped single brake discs. The single brake discs are sequentially arranged end to end at intervals in the annular direction to form split brake discs. The preparation method comprises the steps that the single brake discs are manufactured, the manufactured single brake discs are taken out, and after finish machining treatment, the single brake discs are sequentially arranged end to end at intervals in the annular direction to form the split brake discs. The hardness, bonding strength and salt spray corrosion resistance of the brake disc can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of brake discs, and in particular to a split brake disc of a wind power yaw brake and a preparation method thereof. Background Art

[0002] In wind power generation technology, the wind turbine yaw brake is a key component of the wind turbine generator set, which is used to control the direction of the wind rotor to maximize the efficiency of capturing wind energy, and slow down or stop the wind rotor when the wind speed is too high to ensure the safe operation of the wind turbine generator set. At present, the brake disc used in the wind turbine yaw brake is mostly made of ductile iron with a hardness between 110-160HBW. This material has problems such as poor wear resistance, high maintenance cost and high material brittleness in practical applications. In addition, compared with inland areas, the average wind speed at sea is high and the wind energy is stable, which can obtain the greatest economic value. However, the ductile iron material has poor resistance to salt spray corrosion, which will accelerate the wear rate of the brake disc.

[0003] In addition, most existing brake discs are closed annular brake discs, and the wear debris and oil stains generated during long-term use are difficult to discharge. Among them, the wear debris will shorten the service life of the brake disc, and the oil stains will reduce the braking performance of the brake disc.

[0004] Therefore, it is necessary to develop a split brake disc for a wind turbine yaw brake and a preparation method thereof to solve the problems existing in the prior art. Summary of the invention

[0005] The object of the present invention is to provide a split brake disc for a wind turbine yaw brake and a preparation method thereof. The specific technical scheme is as follows:

[0006] In a first aspect, the present invention provides a split brake disc for a wind turbine yaw brake, comprising a plurality of arc-shaped single brake discs; the single brake discs are arranged in sequence along the circumferential direction with head to tail spacing to form a split brake disc.

[0007] Optionally, each of the single brake discs comprises a structural layer and a friction layer which are combined with each other; the structural layer and the friction layer are arranged in sequence close to the center of the single brake disc along the radial direction of the single brake disc.

[0008] Optionally, the spacing distance between each two adjacent single brake discs is 1-3 mm; and the number of the single brake discs is 3-8.

[0009] In a second aspect, the present invention provides a method for preparing the split brake disc of the wind turbine yaw brake, comprising:

[0010] Step S1: Making a single brake disc

[0011] The structural layer adopts the following first raw material components in mass fraction: 62%-85% aluminum powder, 2%-6% copper powder, 1%-2% magnesium powder, 0.2%-3% zinc powder and 10%-30% first ceramic reinforcement phase;

[0012] The friction layer adopts the second raw material component with the following mass fractions: aluminum powder 35%-65%, copper powder 2%-6%, magnesium powder 1%-2%, zinc powder 0.2%-3% and second ceramic reinforcement phase 30%-60%;

[0013] The first raw material component is mixed and poured into the first cavity in the female mold, and the second raw material component is mixed and poured into the second cavity in the female mold; the first cavity and the second cavity are separated by a removable isolation sheet;

[0014] Pull out the isolation sheet, and subject the first raw material component and the second raw material component in the female mold to a pressure treatment, so that the first raw material component forms a first green body, and the second raw material component forms a second green body;

[0015] The first blank and the second blank in the female mold are sequentially sintered and shaped, so that the first blank forms the structural layer, the second blank forms the friction layer, and the adjacent surfaces of the structural layer and the friction layer are combined, so that the structural layer and the friction layer form the single brake disc;

[0016] Step S2, taking out the single brake discs, and after fine processing, arranging the single brake discs in sequence along the circumferential direction with head and tail spacing to form split brake discs.

[0017] Optionally, there are multiple structural layers; the content of the first ceramic reinforcement phase in each structural layer increases sequentially along the arrangement direction close to the friction layer.

[0018] Optionally, the first ceramic reinforcement phase includes at least one of silicon carbide, zirconium carbide and boron carbide; and the second ceramic reinforcement phase includes at least one of silicon carbide, zirconium carbide and boron carbide.

[0019] Optionally, the particle size range of the first ceramic reinforcement phase is 5-20 μm; the particle size range of the second ceramic reinforcement phase is 50-200 μm; the particle size range of the aluminum powder, the particle size range of the copper powder, the particle size range of the magnesium powder and the particle size range of the zinc powder are all 20-60 μm.

[0020] Optionally, the pressurization treatment uses a pressurization pressure of 150-300 MPa and a pressurization time of 10-20 s.

[0021] Optionally, the sintering process is performed under an inert atmosphere, with a sintering temperature of 560-650° C. and a sintering time of 1-3 h.

[0022] Optionally, the shaping treatment adopts a shaping temperature of 500-550° C., a shaping pressure of 200-400 MPa, and a holding time of 10-20 s.

[0023] The application of the technical solution of the present invention has at least the following beneficial effects:

[0024] (1) The present invention provides a split brake disc for a wind turbine yaw brake, in which two adjacent single brake discs are arranged at an interval to form a gap, which is convenient for timely discharge of wear debris and oil during use, thereby reducing the impact on the service life and braking performance of the brake disc.

[0025] (2) The present invention provides a method for preparing a split brake disc for a wind turbine yaw brake. In the production of the structural layer and the friction layer, aluminum alloy powder material and ceramic reinforcement phase material are used in combination, so as to improve the resistance of the brake disc to salt spray corrosion and avoid the problem of accelerated wear in a salt spray corrosion environment. At the same time, compared with a brake disc made of ductile iron material, a brake disc made of aluminum alloy powder material is 50%-60% lighter and has smoother braking. The content of the ceramic reinforcement phase used in the production of the structural layer and the friction layer is a gradient design, which can optimize the performance of the brake disc. Specifically, a lower content of the first ceramic reinforcement phase is used in the production of the structural layer, so as to improve the toughness of the structural layer, reduce brittleness, and avoid The fastening area is prone to cracking when assembly is not required; a higher content of the second ceramic reinforcement phase is used in the production of the friction layer to improve the wear resistance of the friction layer, reduce the replacement frequency of the brake disc, and significantly reduce costs; the isolation plate is pulled out before the pressurization treatment to form a slight serrated bite layer on both sides of the bonding surface of the first blank and the second blank to enhance the interface bonding strength; sintering treatment is used to enhance the flow of low-melting-point zinc elements, achieve metallurgical bonding of the bonding surface, and significantly improve the interface bonding strength; shaping treatment is used to make the metal fluidity between the structural layer and the friction layer different, further increase the serrated curvature on both sides of the bonding surface, thereby increasing the bonding strength of the bonding surface and improving the stability of the brake disc.

[0026] In addition to the above-described purposes, features and advantages, the present invention has other purposes, features and advantages. The present invention will be further described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0028] Figure 1 It is a structural schematic diagram of a split brake disc of a wind power yaw brake in Example 2;

[0029] Among them, 1. Structural layer; 2. Friction layer. DETAILED DESCRIPTION

[0030] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0031] Embodiment 1:

[0032] A method for preparing a split brake disc of a wind power yaw brake, comprising:

[0033] Step S1: Making a curved single brake disc

[0034] The structural layer adopts the following first raw material components in mass fraction: 67% aluminum powder, 4% copper powder, 1.5% magnesium powder, 2.5% zinc powder and 25% first ceramic reinforcement phase;

[0035] The friction layer uses the following second raw material components in mass fractions: 42% aluminum powder, 4% copper powder, 1.5% magnesium powder, 2.5% zinc powder, and 50% second ceramic reinforcement phase;

[0036] The first raw material component is mixed evenly (specifically, mixed evenly in a mixer, the speed is 100r / min, and the mixing time is 1h) and poured into the first cavity in the female mold; the second raw material component is mixed evenly (specifically, mixed evenly in a mixer, the speed is 100r / min, and the mixing time is 1h) and poured into the second cavity in the female mold; the first cavity and the second cavity are separated by a removable isolation sheet (specifically, an arc-shaped isolation sheet);

[0037] Pull out the isolation sheet, and subject the first raw material component and the second raw material component in the female mold to a pressure treatment, so that the first raw material component forms a first green body, and the second raw material component forms a second green body;

[0038] The first blank and the second blank in the female mold are sequentially sintered and shaped, so that the first blank forms the structural layer, the second blank forms the friction layer, and the adjacent surfaces of the structural layer and the friction layer are combined, so that the structural layer and the friction layer form the single brake disc; the structural layer and the friction layer are sequentially arranged close to the center of the single brake disc along the radial direction; the number of the structural layer is one;

[0039] Step S2, take out the single brake disc, and after fine processing (including turning, drilling, etc.), arrange the single brake discs (specifically 8 single brake discs) in sequence along the circumferential direction at intervals from head to tail to form a split brake disc; the interval between each two adjacent single brake discs is 2 mm. When the split brake disc is used as a wind power yaw brake of a wind turbine generator set, it is fixed to the yaw bearing by a fixing member (such as a bolt).

[0040] The particle size range of the first ceramic reinforcement phase is 5-20 μm; the particle size range of the second ceramic reinforcement phase is 50-200 μm; the particle size range of the aluminum powder, the particle size range of the copper powder, the particle size range of the magnesium powder and the particle size range of the zinc powder are all 20-60 μm.

[0041] The first ceramic reinforcement phase is zirconium carbide; the second ceramic reinforcement phase is silicon carbide.

[0042] The pressurization pressure used in the pressurization treatment is 260 MPa, and the pressurization time is 10 s.

[0043] The sintering process is completed in an inert atmosphere (specifically, a nitrogen atmosphere with a dew point of -35°C), the sintering temperature is 630°C, and the sintering time is 2.5 hours.

[0044] The shaping process adopts a shaping temperature of 550° C., a shaping pressure of 400 MPa, and a holding time of 20 seconds.

[0045] The Brinell hardness of the friction layer material is 215 HBW.

[0046] Embodiment 2:

[0047] Different from Example 1, see Figure 1 , the number of the structural layers 1 is two, and the content of the first ceramic reinforcement phase in each of the structural layers 1 increases successively along the arrangement direction close to the friction layer 2. Specifically, the first raw material component and content of the structural layer 1 far away from the friction layer 2 are the same as those in Example 1, while the content of the first raw material component of the structural layer 1 close to the friction layer 2 changes as follows: 57% aluminum powder, 35% first ceramic reinforcement phase, and the rest is the same as in Example 1. The Brinell hardness of the friction layer material is 217 HBW.

[0048] Comparative Example 1:

[0049] Different from Example 1, the structural layer and the friction layer have not been subjected to shaping treatment, and the Brinell hardness of the friction layer material is 182 HBW.

[0050] Comparative Example 2:

[0051] Different from Example 1, the content of the second ceramic reinforcement phase in the friction layer is 25%, and the Brinell hardness of the friction layer material is 165 HBW.

[0052] Comparative Example 3:

[0053] The difference from Example 2 is that the single brake discs are connected end to end in sequence along the circumferential direction to form a closed brake disc. The Brinell hardness of the friction layer material is 214 HBW.

[0054] Comparative Example 4:

[0055] The closed brake disc is made of ductile iron material according to conventional technology and has a hardness of 158 HBW.

[0056] The performance tests were performed on the brake discs prepared in Examples 1-2 and Comparative Examples 1-4, and the test results are shown in Table 1. The performance test method is as follows: a resin-based friction plate is used in the brake to be pressed tightly against the friction layer on the brake disc, and a wear test is performed on a friction and wear tester to obtain the friction coefficient and the wear amount of the brake disc body; after the test, it is exposed to an alkaline salt spray of PH10 for 120 hours, and then the same wear test method as above is used to test, and the friction coefficient and the wear amount of the brake disc body are measured. Among them, the rated linear speed of the brake disc is set to 15mm / s, the specific pressure of the brake pad friction plate is 3MPa, and the total test distance is 5km.

[0057] Table 1 Performance test results

[0058]

[0059]

[0060] It can be seen from the data in Table 1 that compared with Comparative Example 4, the brake disc prepared by Examples 1-2 of the present invention uses a combination of aluminum alloy powder materials and ceramic reinforcement phases in both the structural layer and the friction layer, which is convenient for improving the salt spray corrosion resistance of the brake disc, avoiding the problem of accelerated wear in a salt spray corrosion environment, and can also improve the wear resistance of the brake disc, increase the friction coefficient, and reduce the amount of wear.

[0061] Furthermore, compared with the brake disc prepared in Example 1, the brake disc prepared in Example 2 adds an intermediate structural layer with a high ceramic reinforcement phase content in the structural layer. The brake disc material has high rigidity, small deformation, is less prone to uneven wear, has a higher friction coefficient, and reduces wear.

[0062] By comparing Example 1 with Comparative Example 1, it can be seen that the brake disc prepared by the shaping process has high interface bonding strength, small disc deformation, less prone to eccentric wear, increased friction coefficient, and reduced wear.

[0063] Comparing Example 1 with Comparative Example 2, it is known that using a suitable high content of ceramic reinforcement phase in the friction layer can increase the hardness of the friction layer material, thereby improving the wear resistance of the brake disc, increasing the friction coefficient, and reducing the wear amount.

[0064] Comparing Example 2 with Comparative Example 3, it is known that the friction coefficient is reduced and the wear volume is increased by eliminating the clearance of the single brake disc. This may be due to the wear debris generated during the test, which causes abnormal wear, serious damage to the disc surface, and increased wear volume; the oil pollution generated during the test reduces the dynamic friction coefficient.

[0065] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A split brake disc for a wind turbine yaw brake, characterized in that: It comprises a plurality of arc-shaped single brake discs; each of the single brake discs is arranged in sequence along the circumferential direction with an end-to-end spacing to form a split brake disc.

2. The split brake disc of the wind turbine yaw brake according to claim 1 is characterized in that: Each of the single brake discs comprises a structural layer and a friction layer which are combined with each other; the structural layer and the friction layer are sequentially arranged close to the center of the single brake disc along the radial direction of the single brake disc.

3. The split brake disc of the wind turbine yaw brake according to claim 2 is characterized in that: The spacing distance between each two adjacent single brake discs is 1-3 mm; the number of the single brake discs is 3-8.

4. A method for preparing the split brake disc of a wind turbine yaw brake as claimed in claim 2 or 3, characterized in that: include: Step S1: Making a single brake disc The structural layer adopts the following first raw material components in mass fraction: 62%-85% aluminum powder, 2%-6% copper powder, 1%-2% magnesium powder, 0.2%-3% zinc powder and 10%-30% first ceramic reinforcement phase; The friction layer adopts the second raw material component with the following mass fractions: aluminum powder 35%-65%, copper powder 2%-6%, magnesium powder 1%-2%, zinc powder 0.2%-3% and second ceramic reinforcement phase 30%-60%; Mixing the first raw material component and pouring it into the first cavity in the female mold, and mixing the second raw material component and pouring it into the second cavity in the female mold; The first chamber is separated from the second chamber by a removable isolation sheet; Pull out the isolation sheet, and subject the first raw material component and the second raw material component in the female mold to a pressure treatment, so that the first raw material component forms a first green body, and the second raw material component forms a second green body; The first blank and the second blank in the female mold are sequentially sintered and shaped, so that the first blank forms the structural layer, the second blank forms the friction layer, and the adjacent surfaces of the structural layer and the friction layer are combined, so that the structural layer and the friction layer form the single brake disc; Step S2, taking out the single brake discs, and after fine processing, arranging the single brake discs in sequence along the circumferential direction with head and tail spacing to form split brake discs.

5. The method for preparing the split brake disc of the wind turbine yaw brake according to claim 4, characterized in that: There are multiple structural layers; the content of the first ceramic reinforcement phase in each structural layer increases sequentially along the arrangement direction close to the friction layer.

6. The method for preparing the split brake disc of the wind power yaw brake according to claim 4, characterized in that: The first ceramic reinforcement phase includes at least one of silicon carbide, zirconium carbide and boron carbide; the second ceramic reinforcement phase includes at least one of silicon carbide, zirconium carbide and boron carbide.

7. The method for preparing the split brake disc of the wind turbine yaw brake according to claim 4, characterized in that: The particle size range of the first ceramic reinforcement phase is 5-20 μm; the particle size range of the second ceramic reinforcement phase is 50-200 μm; the particle size range of the aluminum powder, the particle size range of the copper powder, the particle size range of the magnesium powder and the particle size range of the zinc powder are all 20-60 μm.

8. The method for preparing a split brake disc for a wind turbine yaw brake according to claim 4, characterized in that: The pressurization pressure used in the pressurization treatment is 150-300 MPa, and the pressurization time is 10-20 s.

9. The method for preparing a split brake disc for a wind turbine yaw brake according to claim 4, characterized in that: The sintering process is completed in an inert atmosphere, the sintering temperature is 560-650° C., and the sintering time is 1-3 hours.

10. The method for preparing the split brake disc of the wind power yaw brake according to claim 4, characterized in that: The shaping process adopts a shaping temperature of 500-550° C., a shaping pressure of 200-400 MPa, and a holding time of 10-20 seconds.